1992
DOI: 10.1007/bf02255265
|View full text |Cite
|
Sign up to set email alerts
|

Chironomid pupal exuviae and larvae of two storage reservoirs in The Netherlands

Abstract: For three years chironomid larvae were collected bimonthly with a grab sampler in two deep storage reservoirs in The Nethedands. Chironomid pupal exuviae were collected monthly, from April to November, with a handnet. Net samples yielded more taxa than grab samples. The taxa found in net samples originated from more habitats, than taxa found in grab samples. The relative contribution of Orthocladiinae was much larger in net samples. Based on the results obtained in the two reservoirs, some advantages and disad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Some examples of this disparity are : Wilson & Bright (1973) took 200 exu viae in the River Rhine as well as Ruse (1993Ruse ( , 1995 in the Pang river. In the River Meuse, Kuijpers et al (1992) as well as Evrard (1996) identified 300 pupal exuviae whereas Frantzen (1992) in the Lower Rhone river and Gendron & Laville (1995) in a 4 th order sec tion of the River Aude, showed that 500 exuviae was best.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Some examples of this disparity are : Wilson & Bright (1973) took 200 exu viae in the River Rhine as well as Ruse (1993Ruse ( , 1995 in the Pang river. In the River Meuse, Kuijpers et al (1992) as well as Evrard (1996) identified 300 pupal exuviae whereas Frantzen (1992) in the Lower Rhone river and Gendron & Laville (1995) in a 4 th order sec tion of the River Aude, showed that 500 exuviae was best.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Aagaard (1978) undertook a detailed study of larvae and adults (spatial and temporal) from a single Norwegian lake, and found 76 species. A multiple‐year study of larvae and pupal exuviae from two Dutch water‐storage reservoirs resulted in 58 species (Kuijpers, Ketelaars & Van Breemen, 1992), while in one of the most detailed studies of an African lake, Hare & Carter (1987) recorded 80 chironomid species from a Nigerian lake. They collected adults and larvae, and suspected that many of the flying adults originated in the terrestrial environs of the lake rather than the lake itself, but concluded that 46 species of the chironomids represented in their samples lived within the lake.…”
Section: Discussionmentioning
confidence: 99%